PENGARUH KONSENTRASI SURFAKTAN TERHADAP KARAKTERISTIK FISIK NANOEMULSI DAN NANOEMULSI GEL KOENZYM Q10 - Silvi ayu Wulansari; Ririn Sumiyani; Ni Luh Dewi Aryani (Universitas Airlangga, 2019)
Coenzyme Q10 is a compound that functions as an antioxidant with a large molecular weight of 863.36 g/mol and has lipophilic properties. This makes coenzyme Q10 need to be formulated to improve the solubility of the material and the delivery system in the skin. This study aims to determine the effect of surfactant variations (a combination of PEG-40 HCO and Span 80) on the physical characteristics of nanoemulsion and nanoemulsion gel preparations. Coenzyme Q10 is formulated using the rice bran oil oil phase with the combination surfactant. This research was made in 3 nanoemulsion formulas FI, F2, F3 and 3 nanoemulsion gel formulas F4, F5, F6. Evaluation of physical characteristics is done after 24 hours after the preparation is complete, observations made include organoleptic (shape, color and phase formed), pH, viscosity, droplet size, zeta potential and polydispersity index. The research data were processed statistically using the Kruskal-Wallis analysis and Mann-Whitney follow-up tests. The results showed that the surfactant concentration affected physical characteristics (viscosity, droplet size, zeta potential and polydispersity index) with a significantly different result (p <0.05) but the surfactant concentration did not affect the pH with the results not significantly different (p> 0.05)